SARS-CoV-2 infection induces a pro-inflammatory cytokine response through cGAS-STING and NF-κB - Neufeldt, Christopher; Cerikan, Berati; Cortese, Mirko; Frankish, Jamie; Lee, Ji Young; Plociennikowska, Agnieszka; Heigwer, Florian; Prasad, Vibhu; Joecks, Sebastian; Burkart, Sandy; Zander, David Y.; Subramanian, Baskaran; et al. (Communications biology, 2022)
SARS-CoV-2 is a novel virus that has rapidly spread, causing a global pandemic. In the majority of infected patients, SARS-CoV-2 leads to mild disease; however, in a significant proportion of infections, individuals develop severe symptoms that can lead to long-lasting lung damage or death. These severe cases are often associated with high levels of pro-inflammatory cytokines and low antiviral responses, which can cause systemic complications. Here, we have evaluated transcriptional and cytokine secretion profiles and detected a distinct upregulation of inflammatory cytokines in infected cell cultures and samples taken from infected patients. Building on these observations, we found a specific activation of NF-κB and a block of IRF3 nuclear translocation in SARS-CoV-2 infected cells. This NF-κB response was mediated by cGAS-STING activation and could be attenuated through several STING-targeting drugs. Our results show that SARS-CoV-2 directs a cGAS-STING mediated, NF-κB-driven inflammatory immune response in human epithelial cells that likely contributes to inflammatory responses seen in patients and could be therapeutically targeted to suppress severe disease symptoms., Neufeldt et al. evaluate transcriptional and cytokine secretion profiles of cells and patient sera following SARS-CoV-2 infection and detect distinct upregulation of inflammatory cytokines. They also demonstrate that this upregulation is mediated by cGAS-STING and NF-κB signalling, which could provide a potential avenue for the development of future therapies against SARS-CoV-2.
Gesehen am 19.04.2022